Analisis Pemberian Diskon sebagai Strategi Pemasaran Pada PT Jaring Abadi Retailindo - Hidayatulloh, M. Alfin; Pratiwi, Dwi Ajeng Regi; Nafisa, Adita; Wardani , Rama Aditya (Jurnal Bisnis Islam dan Kewirausahaan, 2024)
This research aims to analyze discounts as a marketing strategy at PT Jaring Abadi Retailindo. The method used in this research is a qualitative method, namely by studying or researching aspects of written or oral speech which will produce descriptive data. The data collection technique was carried out using triangulation and data         analysis was inductive. The results of this research indicate that the marketing strategy used at PT Jaring Abadi Retailindo through providing discounts is to attract consumer attention. This strategy is used with the aim of generating consumers' desire to shop for products that are being discounted, furthermore consumers are also interested in looking at other products so that a desire to buy arises or what is usually referred to as an unplanned purchase (impulse purchase). Providing discounts is always associated with events organized by PT Jaring Abadi Retailindo, including discounts for members, discounts in the form of vouchers, discounts when it rains, discounts in the form of vouchers, discounts in the form of buy one get one, discounts at Eid al-Fitr events, Christmas, and the end of the year. Discounts are still very relevant to be used today by PT Jaring Abadi Retailindo, as a company strategy in positioning consumers as an important component that must be considered. This of course has an impact on the company's success in maintaining market position, product value and consumer loyalty so that it is not easily transferred to competing companies